The Museum : A Short History of Crisis and Resilience - Redman, Samuel J. (Book collections on Project MUSE., 2022)
"On a cold and clear afternoon in January 1865, a roaring fire swept through the Smithsonian Institution. The flames at the Smithsonian, however, were merely an omen of things to come for museums in the United States. Beset by challenges ranging from pandemic and war to fire and economic uncertainty, museums have sought ways to emerge from crisis periods stronger than before, occasionally carving important new paths forward in the process. Hampered by troubling problems, museum leaders made different choices while remaining committed to versions of the museum idea. This book explores the concepts of "crisis" as it relates to museums in the United States, exploring how museums have dealt with challenges ranging from depression and war to pandemic and philosophical uncertainty. Fires, floods, and hurricanes have all upended museum plans and forced people to ask difficult questions about U.S. cultural life. With chapters exploring the First World War and 1918 influenza pandemic, Great Depression, Second World War, 1970 Art Strike in New York City, as well as more recent controversies in U.S. museums, this book takes a new approach to understanding museum history. By diving deeply into the nature of museum changes emerging from these key challenges, historian Samuel J. Redman argues that museums and other cultural institutions can use their history to prepare for challenges lying ahead."--